Flow-injection spectrophotometric determination of calcium using murexide as a color agent - Grudpan K. (2014)
FI spectrophotometric determination of calcium using murexide has been developed. The problem of the color of the dye fading and/or its complex in an alkaline medium in the batch method can be overcome by taking advantage of FIA. A calcium solution is injected into an ethylenediamine-ethylenediamine hydrochloride buffer (1 M, pH 11) which also serves as a masking agent, and is then merged with the aqueous murexide (0.005%, w/v) and continuously monitored. Simple FIA manifolds, including an LED colorimeter detector hooked up to a PC-based data acquisition and evaluation system are described. Optimization of FIA systems has been made. The proposed procedures have been validated by using reference materials and comparing the results with the standard methods, and then applied to ores and drug samples.